2007
DOI: 10.1021/jf070195v
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vine Vigor on Grape (Vitis viniferaL. Cv. Pinot Noir) Anthocyanins. 1. Anthocyanin Concentration and Composition in Fruit

Abstract: The relationships between grapevine (Vitis vinifera) vigor variation and resulting fruit anthocyanin accumulation and composition were investigated. The study was conducted in a commercial vineyard consisting of the same clone, rootstock, age, and vineyard management practices. The experimental design involved assigning vigor zones in two vineyard sites based upon differences in vine growth. Fruits and wines were analyzed by HPLC from designated vigor zones in 2003 and 2004. Average berry weight (grams), avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
75
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 48 publications
18
75
1
1
Order By: Relevance
“…The effects of mineral nutrition and vine vigor on anthocyanin composition and concentration have also been investigated (Cortell et al 2007a, Downey et al 2006, Keller et al 1998. Heavy N fertilization at flowering delayed ripening and anthocyanin accumulation, with malvidin-3-glucoside enhanced in proportion to the other forms (Keller et al 1998).…”
Section: Anthocyanin Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of mineral nutrition and vine vigor on anthocyanin composition and concentration have also been investigated (Cortell et al 2007a, Downey et al 2006, Keller et al 1998. Heavy N fertilization at flowering delayed ripening and anthocyanin accumulation, with malvidin-3-glucoside enhanced in proportion to the other forms (Keller et al 1998).…”
Section: Anthocyanin Compositionmentioning
confidence: 99%
“…The most likely mechanism that explains nitrogen effect is the excess of vigor. One study reported that a reduction of vine vigor increased anthocyanin accumulation, but variations of composition were not clear regarding year and site (Cortell et al 2007a). Koundouras et al (2009) observed a higher concentration of malvidin-3-O-glucoside and malvidin-3-Ocoumarate glucoside for Cabernet Sauvignon vines grafted onto the high-vigor rootstock 1103P than those grafted on SO4.…”
Section: Anthocyanin Compositionmentioning
confidence: 99%
“…In the present study, we demonstrated that the climatic conditions in each grape-growing region affected 'Koshu' grape composition; however, bud number and other cultivation practices could not be perfectly equilibrated in the vineyards examined. For example, the production of flavonoid compounds, including anthocyanins, in grape skins might be affected by vine vigor (Cortell et al, 2005(Cortell et al, , 2007. Therefore, for the improvement of 'Koshu' grape and wine quality, it would be necessary in future experiments to accumulate microclimate data for each region for several years and to evaluate the relationship between 'Koshu' grape composition and microclimate conditions.…”
Section: Discussionmentioning
confidence: 99%
“…1 From both a viticulture and winemaking perspective, low vigor in the vineyard has traditionally been linked to an improved phenolic composition in the resulting wines. [7][8][9] Provided that the berry native phenolic composition imparts a huge impact on wine composition and overall quality 10,11 winemakers often seek grapes arising from moderate-to-low vigor vineyards. In vines, low vigor has been classically associated with deficit irrigation, 12,13 insect attack, 14 and viral 15 and fungal diseases.…”
Section: Dovepressmentioning
confidence: 99%